Garners strike, 1978 (London, 1978)
1978 1974-79 "Garners strike, 1978" [BW0080], 1978, Trades Union Congress The strike at Garners Steak Houses in London began on January 26, 1978 when the management finally turned down a demand from the Transport and General Workers Union for union recognition. The 84 strikers were immediately sacked. The strike was seen as an important campaign to improve the wages and conditions of migrant workers in the catering industry, but was ultimately unsuccessful and ended in June 1979. This leaflet, stickers and badges were used in the publicity campaign.